Denda Adat dalam Penjatuhan Pidana (Studi Kasus Kejahatan Kekerasan Di Pengadilan Negeri Merauke-Papua) - Aroma Elmina Martha (Jurnal Hukum IUS QUIA IUSTUM, 2004)
Giving the criminal sanction, specialiy the gift of sanction with tradition fine in the cases of vioience, iike" Blood Fine" is valid to the citizens who have local law and the other ethnics who are loyal. "Blood Fine" can be a payment for fine, the assistance of financial on medical treatment and apologize. The judge in taking his decision must consider the local criminal law, more special the custom fine, but in the cases ofviolence on womanpositive law ignore the local law.